Subjects of Tax Legal Relations - L. V. Burnysheva; I. G. Lvova (Сибирское юридическое обозрение, 2019)
The article deals with issues related to classification and certain aspects of the legal status of subjects of tax legal relations, the concepts of “subjects of tax law”, “subjects of tax legal relations”, “participants in tax legal relations” are compared. The analysis of various classifications of subjects of tax legal relations is carried out with a more detailed study of classification by the method of normative certainty. The composition of the subjects fixed by the tax legislation and subjects not included in the list of participants in tax legal relations, as defined in Article 9 of the Tax Code of the Russian Federation, is detailed. As a result of the study, measures are proposed to improve tax legislation.